The clock‐controlled chemokine contributes to neuroinflammation‐induced depression. Issue 6 (23rd April 2020) - Chen, Xiaojuan; Hu, Qianying; Zhang, Ke; Teng, Huajing; Li, Mingzhen; Li, Dan; Wang, Jiesi; Du, Quansheng; Zhao, Mei
Abstract: The circadian rhythm plays a central role in immune function, and its disruption has been closely linked to the etiology of depression. However, the mechanisms underlying the association between depression and circadian rhythm remain unclear. We found that mice deficient of Per2, a central clock component of circadian output, were resilient to neuroinflammation‐induced depressive behavior. After repeated central lipopolysaccharide (LPS) injections, MCP‐1, MIP‐1β, and RANTES increased in wild type (WT) but not in Per2 ‐deficient mice. In addition, intracerebroventricular injection of RANTES resulted in depression‐like behavior, and Met‐RANTES, a CCR5 antagonist, could reverse depression‐like behavior induced by LPS treatments. These results indicated that the Per2 gene contributes to depression via chemokines, especially RANTES. Furthermore, BMAL1 expression decreased in LPS‐treated Per2 ‐deficient mice and BMAL1 could bind to the promoter of Rantes, indicating clock gene can act as a regulator for neuroinflammation. In conclusion, Rantes, a clock‐controlled gene (CCG), is involved in clock‐immunological mechanisms underlying the effects of Per2 on neuroinflammation‐induced depression‐like behavior.